(untitled) (Journal of Hama University, 2021)
This research aimed to identify the reality of applying quality improvement methods, the reality of scientific research, and the procedures currently applied in the universities of Tishreen and Hama, and the extent of their contribution to improving their ranking in the global ranking of universities, and the descriptive analytical approach was used, and the questionnaires were distributed to 116 faculty members at my university. Tishreen and Hama, and the most important results of the survey were as follows: the low degree of availability of quality improvement methods that must be available from the perspective of total quality management, the low degree of availability of scientific research from the perspective of total quality management, and the low degree of conformity of the procedures currently prevailing in the two universities under study with the procedures that must be available from the perspective of Total Quality Management to improve the global rankings of Syrian universities.